Impact of structured triage on the overcrowding of the emergency department of a tertiary hospital - Taype-Huamaní, Waldo Augusto (2021)
Objetive: To assess the impact of structured triage on overcrowding indicators in the emergency department (ED) of a tertiary hospital. Material and Methods: Retrospective observational study of pre and post design. Carried out in a social security hospital, comparing care during two quarters. The implementation of structured triage of five Manchester-type priorities was evaluated, comparing the number of visits, patients attended, priority of care, admission topic, patients not attended, patients who died in the first 6 hours and time to first attention. Statistical analysis (95% confidence interval) was performed with data from the institutional system using SPSS 24.0, with institutional approval. Results: 42000 attendances per quarter, 12% were admitted to observation wards. Median age 57 years (range 14 - 103), female 57%. Average daily number of patients admitted to the ED was 240 vs 230 (p<0.01). Priority on admission: I 3%, II 44%, III 37%, IV 16% and V 0%. In the second trimester, priority I care decreased and priority II and III increased. The daily average of patients not evaluated was 20.5 and 13.7 in each quarter. Deaths in the first 6 hours were 0.13 and 0.15% of total admissions, according to the study period. The average time in the ED after first care was 5.2 hours, decreasing in the second quarter in all areas. Conclusion: The Manchester structured triage system reduces the proportion of patients not attended, the number of patients attended with priority I and the time in the ED after first care